2018
DOI: 10.1186/s12903-018-0626-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between maxillary posterior teeth and the maxillary sinus floor using cone-beam computed tomography

Abstract: BackgroundMaxillary posterior teeth have close anatomical proximity to the maxillary sinus floor (MSF), and the race, gender, age, side and presence/absence of adjacent teeth may influence the mean distances between the root apices and the MSF. This study aimed to evaluate both the relationship between the maxillary posterior teeth and MSF, and the influence of adjacent teeth loss on the distance between the maxillary posterior roots and MSF.MethodsCone-beam computed tomography images were collected from 1011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
43
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 23 publications
10
43
1
9
Order By: Relevance
“…36 both found that only buccal roots of maxillary 1 st molars had the highest prevalence of being distant from the MSF with the 1 st study conducted on 30 maxillary 1 st molar& 30 maxillary 2 nd molar in 17 CBCT scans, while the last one conducted on 2488 molars in 849 CBCT scans of Turkish subjects. This result was partly contradicting our findings as they found that the palatal root of maxillary 1 st molar had the highest prevalence of being inside the sinus, a finding that was also reported by Gu et al 2018 38 and Estela et al 2016 31 unlike us.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…36 both found that only buccal roots of maxillary 1 st molars had the highest prevalence of being distant from the MSF with the 1 st study conducted on 30 maxillary 1 st molar& 30 maxillary 2 nd molar in 17 CBCT scans, while the last one conducted on 2488 molars in 849 CBCT scans of Turkish subjects. This result was partly contradicting our findings as they found that the palatal root of maxillary 1 st molar had the highest prevalence of being inside the sinus, a finding that was also reported by Gu et al 2018 38 and Estela et al 2016 31 unlike us.…”
Section: Discussioncontrasting
confidence: 99%
“…The highest prevalence of MSF penetration 'type 3' in the current study was recorded for buccal roots of maxillary 2 nd molars and this finding was matching those of Kilic 2010 5 , Pagin 2013 41 , Jung 2012 33 , Asthana 2015 42 & Tian 2016 37 . However , partial correspondence was found between our finding in this point and those of Gu 2018 38 and Estela 2016 31 as both of them found that the palatal root of 1 st maxillary molar is sharing the buccal roots of 2 nd maxillary molars in the highest prevalence of MSF penetration. Yet, Shokri et al 2014 34 reported that both maxillary 1 st molar & 2 nd molar had the highest prevalence of MSF penetration without differentiating the roots affection.…”
Section: While Asthana Et Al 2015 42 and Ok Et Al 2014supporting
confidence: 63%
See 3 more Smart Citations